Strategi Penanggulangan Pencemaran Air Sungai Rejo Agung Menggunakan Pemodelan Qual2kw - Muhammad Arya Pradipta; Okik Hendriyanto (Jurnal Serambi Engineering, 2024)
Water pollution is a serious environmental problem caused by human activities, especially in urban areas. The Rejo Agung River in Jombang District, East Java, was the focus of the study due to the impact of pollution from household waste and the tofu industry. In order to control water pollution, QUAL2Kw modeling was used as a tool to identify major pollution sources, predict changes in water quality, and test the effectiveness of countermeasure strategies. The study revealed that the water quality of the Rejo Agung River, although still meeting quality standards, experienced a significant decline in the Dissolved Oxygen (DO) parameter at several sampling points, indicating a pollution problem that needs to be addressed. The modeling results show that the river has varying pollutant load carrying capacity, with water quality degradation mainly in DO levels. The STORET method analysis also showed that the level of pollution varied from mild to moderate pollution. Various pollution mitigation strategies were proposed, including socialization to the community on waste management, monitoring of industrial and household waste discharges, river clean-up activities, improved management of communal WWTPs, as well as technical studies for water class determination and pollution load carrying capacity as the basis for granting permits. With the implementation of appropriate strategies, it is expected that water pollution in Rejo Agung River can be reduced, maintaining the sustainability of the river ecosystem, and improving the quality of life of people who depend on these water resources.